2023
DOI: 10.1037/pag0000759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on face perception: Reduced eye region discrimination ability but intact holistic processing.

Regan Fry,
James W. Tanaka,
Sarah Cohan
et al.

Abstract: While age-related decline in face recognition memory is well-established, the degree of decline in face perceptual abilities across the lifespan and the underlying mechanisms are incompletely characterized. In the present study, we used the part-whole task to examine lifespan changes in holistic and featural processing. After studying an intact face, participants are tested for memory of a face part (eyes, nose, mouth) with the target and foil part presented either in isolation or in the context of the whole f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 102 publications
0
0
0
Order By: Relevance
“…One possible explanation for this difference is that our participants were older than the participants used in the Lai study (mean age = 42.6, compared to mean age = 22.9). Indeed, one study examining the effect of participants’ ages on face matching and face memory found that worse performance on a face-memory task could be explained by the reduced performance on the face-matching tasks [ 50 ]; further, studies have reported specific deficits in face-feature processing with increasing age (e.g., [ 50 , 51 ]).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this difference is that our participants were older than the participants used in the Lai study (mean age = 42.6, compared to mean age = 22.9). Indeed, one study examining the effect of participants’ ages on face matching and face memory found that worse performance on a face-memory task could be explained by the reduced performance on the face-matching tasks [ 50 ]; further, studies have reported specific deficits in face-feature processing with increasing age (e.g., [ 50 , 51 ]).…”
Section: Discussionmentioning
confidence: 99%